Dampak Kebijakan Insentif PPN DTP Rumah Terhadap Profitabilitas Perusahaan Sektor Real Estat - Bahrian Kuncoro Aji; Vissia Dewi Haptari (JURNAL PAJAK INDONESIA, 2022)
The real estate sector is one of the sectors affected by Covid-19 which has a large multiplier effect on the national economy. Therefore, in march 2021, the Government of Indonesia has issued a VAT incentive policy for the real estate sector for the delivery of houses to increase consumer purchasing power for homes during the Covid-19 pandemic, it’s called the PPN DTP Incentive. This research aimed to examine whether the PPN DTP Incentive have an impact on the profitability of property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period and to review whether this PPN DTP incentive that are temporary in nature can be a permanent VAT facility and provide advice on the VAT facility policy mechanism for the real estate sector based on Article 16B of the VAT Law. The data analysis technique used is the Dependent T-Test to test the difference in average paired data between profitability before and after the Policy of PPN DTP Incentive, namely the profitability of 2019 and 2021 and also the profitability of 2020 and 2021. The results of the study show that there is an impact of PPN DTP incentive on the profitability of 2020 and 2021, while the profitability of 2019 and 2021 has no impact of PPN DTP incentive. Sektor real estat merupakan salah satu sektor terdampak Covid-19 yang memiliki efek berganda yang besar bagi perekonomian nasional. Oleh karena itu, pada bulan maret 2021 Pemerintah Indonesia mengeluarkan kebijakan perpajakan insentif PPN DTP atas penyerahan rumah untuk meningkatkan daya beli masyarakat terhadap rumah saat pandemi Covid-19. Tujuan penelitian ini adalah meninjau apakah kebijakan Insentif PPN DTP ini memiliki dampak terhadap profitabilitas perusahaan sektor properti dan real estat yang terdaftar di BEI periode 2019-2021 dan meninjau apakah insentif PPN DTP yang bersifat temporer dapat menjadi suatu fasilitas PPN yang bersifat permanen serta memberikan saran mekanisme kebijakan fasilitas PPN berdasarkan Pasal 16B UU PPN 1984 bagi sektor real estat. Metode Analisis data yang digunakan yaitu Dependent T-Test untuk melakukan uji beda rata-rata data berpasangan antara profitabilitas sebelum dan sesudah kebijakan Insentif PPN DTP yaitu profitabilitas 2019 dan 2021 serta profitabilitas 2020 dan 2021. Hasil penelitian menunjukan terdapat dampak insentif PPN DTP pada profitabilitas 2020 dan 2021 sedangkan profitabilitas 2019 dan 2021 tidak terdapat dampak insentif PPN DTP.